2017
DOI: 10.1016/j.jafrearsci.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the kinematic structures in İzmir (Western Anatolia) with repeated GPS observations (2009, 2010 and 2011)

Abstract: The Western Anatolia and the Aegean Sea regions are one of the most significant seismically active and rapidly deforming fields in the world. Generally, seismic activities cause deformations and these deformations are monitored with Global Positioning System (GPS) / Global Navigation System (GNSS). In this context, GPS data were used to determine the deformation of İzmir and its surrounding to estimate the relative plate motions. In this study, the kinematic structures of the faults, which control the seismic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions. Only 4 of these studies, in which the newest measurement was made in 2012, have focused on İzmir and its immediate surroundings, where the study area is located (Aktuğ and Kılıçoğlu, 2006;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). However, the results herein indicated that a strike-slip tectonic regime was the main reason for the present-day deformation in the southern part of the İBTZ.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions. Only 4 of these studies, in which the newest measurement was made in 2012, have focused on İzmir and its immediate surroundings, where the study area is located (Aktuğ and Kılıçoğlu, 2006;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). However, the results herein indicated that a strike-slip tectonic regime was the main reason for the present-day deformation in the southern part of the İBTZ.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies with new GPS/GNSS measurements have been conducted in western Anatolia over the last 2 decades (McClusky et al, 2000;Aktuğ and Kılıçoğlu, 2006;Reilinger et al, 2006Reilinger et al, , 2010Aktuğ et al, 2009;Özener et al, 2012;Pamukçu et al, 2015;Çırmık et al, 2017a). Regional studies have suggested that a N-S extension is dominant in the region and the mean motion of the region was approximately 25 mm/year towards the SW in Eurasia fixed frame solutions.…”
Section: Discussionmentioning
confidence: 99%
“…62 GNSS sites covering the region were used (Aktuğ and Kılıçoğlu 2006;Aktuğ et. al., 2009;Özener et al, 2013;Çırmık et al, 2017a;Eyübagil et al, 2021 Min. 8-h with 30s interval GNSS measurement was carried out between 5th and 8th of November 2020 at campaign type sites to calculate post-earthquake coordinates Figure 4).…”
Section: Geodetic Network Data and Modellingmentioning
confidence: 99%
“…The direction of extension (T-axis) has a dominating NNE-SSW azimuth with some events showing a roughly N-S azimuth. GPS measurements (e.g., Nyst and Thatcher, 2004;Aktug et al, 2009;Çırmık et al, 2017), as well as palaeomagnetic surveys (e.g., van Hinsbergen et al, 2010;Uzel et al, 2017), suggest that the wider İzmir area is shifted approximately 25 mm/a in a SSW direction, according to a stable Eurasia. GPS-based strain pattern estimations for the broader Aegean (e.g., Floyd et al, 2010;England et al, 2016) suggest that in our study area extension prevails in a roughly NNE-SSW direction, whereas contraction is almost negligible.…”
Section: The Western Anatoliamentioning
confidence: 99%